PENGENALAN POLA DALAM MEMBANGUN SMART TECHNOLOGY PADA ERA INDUSTRI 4.0 DENGAN METODE KLASIFIKASI DYNAMIC IMAGE ANALYSIS – FUZZY NEURAL NETWORK SATU TINJAUAN DALAM TELAAH FILSAFAT ILMU KOMPUTER - HUMUNTAL RUMAPEA (LP2MTBM MAKARIOZ, 2020)
Philosophy and science are two interrelated words, both substantially and historically because the birth of science does notescape the role of philosophy and vice versa, the development of science can strengthen the existence of philosophy.Computer Science as a science that learns both about computing, hardware (hardware) and software (software). ImageProcessing in the Industrial Era 4.0 becomes very important because the technology is continuously evolving which canprovide ease in classifying (Clasification). Dynamic Image Analysis is a dynamically classifying image by using the camera.The methods used are dynamic image analysis-fuzzy Neural Network (DIA-FNN) with weed detection and DHR-ARtiSt,according to camera speed level (FH/s) and particle density. The Data image of the result will be divided into 3 features suchas colour Fieatur, Morfhology feature, and Tecture feature. Results of each classsification analyzed through the FuzzyInference System to get conclusions and decisions on analysis in the form of classifications for coffee, the Fuzzy ControlSystem will soften the motor to place the coffee with the decision that the coffee is very good, good, and not good.